Application of DNA aptamers to block enterotoxigenic Escherichia coli toxicity in a Galleria mellonella larval model - Barros, Maria Margarida (2024)
Enterotoxigenic Escherichia coli (ETEC) is the major bacterial cause of diarrheal diseases in pigs, particularly at young ages, resulting in significant costs to swine farming. The pathogenicity of ETEC is largely dependent on the presence of fimbriae and the ability to produce toxins. Fimbriae are responsible for their initial adhesion to the intestinal epithelial cells, leading to the onset of infection. In particular, the F4 type (K88) fimbriae are often attributed to neonatal infections and have also been associated with post-weaning diarrheal infections. This disease is traditionally prevented or treated with antibiotics, but their use is being severely restricted due to the emergence of resistant bacteria and their impact on human health. Emerging approaches such as aptamers that target the F4-type fimbriae and block the initial ETEC adhesion are a promising alternative. The aim of this study is to assess the effectiveness of two aptamers, Apt31 and Apt37, in controlling ETEC infection in the G. mellonella in vivo model. Initially, the dissociation constant (KD) of each aptamer against ETEC was established using real-time quantitative PCR methodology. Subsequently, different concentrations of the aptamers were injected into Galleria mellonella to study their toxicity. Afterwards, the anti-ETEC potential of Apt31 and Apt37 was assessed in the larvae model. The determined KD was 81.79 nM (95% CI: 31.21199.4 nM) and 50.71 nM (95% CI: 26.5296.15 nM) for the Apt31 and Apt37, respectively, showing no statistical difference. No toxicity was observed in G. mellonella following injection with both aptamers at any concentration. However, the administration of Apt31 together with ETEC-F4+ in G. mellonella resulted in a significant improvement of approximately 30% in both larvae survival and health index compared to ETEC-F4+ alone. These findings suggest that aptamers have promising inhibitory effect against ETEC infections and pave the way for additional in vivo studies.